2022
DOI: 10.1038/s41467-022-35481-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological inhibition of Lin28 promotes ketogenesis and restores lipid homeostasis in models of non-alcoholic fatty liver disease

Abstract: Lin28 RNA-binding proteins are stem-cell factors that play key roles in development. Lin28 suppresses the biogenesis of let-7 microRNAs and regulates mRNA translation. Notably, let-7 inhibits Lin28, establishing a double-negative feedback loop. The Lin28/let-7 axis resides at the interface of metabolic reprogramming and oncogenesis and is therefore a potential target for several diseases. In this study, we use compound-C1632, a drug-like Lin28 inhibitor, and show that the Lin28/let-7 axis regulates the balance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 115 publications
0
3
0
Order By: Relevance
“…Nevertheless, our proteomics data, in both datasets, consistency demonstrated the involvement of the proteins detected at higher levels associated with LIN28B knockdown in multiple pathways required for lipid metabolism. Lipid metabolism in both normal and malignant cells was previously reported to be controlled by LIN28A, LIN28B, and pharmacological suppression of LIN28 [46,47]. LIN28B has been shown to regulate lipid metabolism by targeting specific mRNAs involved in lipid synthesis and storage, thereby controlling the balance of fatty acid and lipid storage in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our proteomics data, in both datasets, consistency demonstrated the involvement of the proteins detected at higher levels associated with LIN28B knockdown in multiple pathways required for lipid metabolism. Lipid metabolism in both normal and malignant cells was previously reported to be controlled by LIN28A, LIN28B, and pharmacological suppression of LIN28 [46,47]. LIN28B has been shown to regulate lipid metabolism by targeting specific mRNAs involved in lipid synthesis and storage, thereby controlling the balance of fatty acid and lipid storage in cells.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of inhibiting other RBPs, such as Lin28, with small-molecule inhibitors has also been explored. Lekka and colleagues reported that the small-molecule C1632 could inhibit Lin28 binding to let-7 precursors 248 . In addition, Wang and colleagues reported that various selective Lin28 inhibitors, such as TPEN and LI71, can suppress Lin28 by targeting various individual domains of Lin28 249 .…”
Section: Therapeutic Strategies For Targeting Rbps and Exoribonucleas...mentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 The prevalence of MASLD is increasing, and it currently affects approximately 25% of adults worldwide. 6 , 7 , 8 , 9 , 10 Metabolic dysfunction–associated steatohepatitis (MASH), which is the progressive stage of MASLD, is characterized by severe hepatic steatosis, inflammation, and fibrosis. MASH can eventually result in cirrhosis or hepatocellular carcinoma.…”
mentioning
confidence: 99%